A clinical cases of tuberculosis in pheasants (Phasianus colchicus) with pathomorphological and molecular verification - M. Radzikhovskyi; I. Sokulskiy; B. Nyzhnyk; O. Valchuk; R. Zaritskyi; O. Dyshkant; S. Derkach; V. Ukhovskyi; L. Korniienko; M. Ruda (Regulatory Mechanisms in Biosystems, 2026)
Tuberculosis remains one of the leading infectious diseases worldwide, persistently imposing a significant impact on the health of humans and animals. Tuberculosis is a prominent cause of increasing morbidity and mortality even despite achiev e ments in human and veterinary medicine and continuous introduction of novel medical technologies for the control of infectious processes into practice. For this reason, this disease must be considered a multivector problem. However, the consequences of avian tuberculosis for public health have been studied poorly. The relevance of such research is highlighted by the fact that most poultry farmers lack awareness of the spread of avian tuberculosis and its implications, the sources of this infection, its routes of transmission, and zoonotic potential. Therefore, the World Tuberculosis Day is observed annualy to raise awareness of this deadly ailment. The article presents clinical cases of tuberculosis in pheasants ( Phasianus colchicus ) from two private farms in Ukraine, focusing on diagnostic peculiarities and zoonotic importance of the disease. Mycobacterioses continue to be a relevant problem for both domestic and wild birds, playing an important role in the epizootiology of tuberculosis. The paper provides insights into the stages of diagnosing, presented as a complex study with identification of the pathogen using molecular-genetic diagnostics. We provide a detailed pathomorphological description of the changes, taking into account macro- and microscopic peculiarities of the course of tuberculosis in pheasants. The objectives of the study were analysis, elucidation, and systematiz a tion of the pathomorphologic peculiarities of tuberculosis in pheasants using a complex of classical and modern methods of diagnostics. For these purposes, we examined 12 corpses of pheasants aged 1 .0– 1.5 years from private farms in Ukraine. A complex approach was employed, combining pathoanatomical, histological, bacteriological, and molecular-genetic methods. Histological preparations were stained with hematoxylin and eosin, and also using the Ziehl–Neelsen method, and the identif i cation of the pathogen was performed using Real-Time PCR. Macroscopically, we determined a notable cachexia and genera l ized granulomatous inflammations of the lungs, liver, spleen, and intestine. Histologically, we found typical tuberculosis gran u lomas with central necrosis, epithelioid cells, and giant Langerhans giant cells. Ziehl–Neelsen stain confirmed the presence of acid-fast mycobacteria. The PCR method established the presence of Mycobacterium avium in the tissues of the internal organs. The yielded results indicate a generalized course of tuberculosis with systemic spread of the pathogen. The study highlights the high diagnostic value of a complex approach involving morphological and molecular-genetic methods, and also underscores the epizootiological and zoonotic significance of avian tuberculosis.